CONSUMER PREFERENCES FOR DIFFERENT TYPES OF COFFEE - Lin, Chien-Chi (PEOPLE: International Journal of Social Sciences, 2024)
This study aims to investigate whether there are differences in preferences for different types of hand-drip and Italian-style coffees across genders and age groups. The findings indicate that gender plays a significant role in coffee preferences, suggesting that café operators should tailor their product promotion strategies based on whether their target demographic is predominantly male or female. Additionally, age-related differences in coffee preferences identified through one-way analysis of variance (ANOVA) underscore the importance of age-specific marketing strategies.